Decreased Intestinal Microbiota Diversity Is Associated With Increased Gastrointestinal Symptoms in Patients With Chronic Pancreatitis. Issue 6 (13th July 2022) - McEachron, Kendall R.; Nalluri, Harika; Beilman, Gregory J.; Kirchner, Varvara A.; Pruett, Timothy L.; Freeman, Martin L.; Trikudanathan, Guru; Staley, Christopher; Bellin, Melena D.
Abstract : Objectives: Chronic pancreatitis (CP) is characterized by abdominal pain, recurrent hospitalizations, frequent exposure to antibiotics, nutritional deficiencies, and chronic opioid use. Data describing the gut microbial community structure of patients with CP is limited. We aimed to compare gut microbiota of a group of patients with severe CP being considered for total pancreatectomy with islet autotransplantation (TPIAT) with those of healthy controls and to associate these differences with severity of clinical symptoms. Methods: We collected stool from healthy donors (n = 14) and patients with CP (n = 20) undergoing workup for TPIAT, in addition to clinical metadata and a validated abdominal symptoms severity survey. Results: Patients with CP had significantly lower alpha diversity than healthy controls ( P < 0.001). There was a significantly increased mean relative abundance of Faecalibacterium in healthy controls compared with patients with CP ( P = 0.02). Among participants with CP, those with lower alpha diversity reported worse functional abdominal symptoms ( P = 0.006). Conclusions: These findings indicate that changes in gut microbial community structure may contribute to gastrointestinal symptoms and provide basis for future studies on whether enrichment of healthy commensal bacteria such as Faecalibacterium could provide clinically meaningful improvements in outcomes for CP patients undergoing TPIAT.